Case report: A novel splice-site mutation of MTX2 gene caused mandibuloacral dysplasia progeroid syndrome: the first report from China and literature review - Fu, Xiaohui; Chen, Shuli; Huang, Xiao; Lu, Qinghua; Cui, Yunfei; Lin, Weinan; Yang, Qin (Frontiers in Endocrinology, 2024)
Background: Mandibuloacral dysplasia (MAD) syndrome is a rare genetic disease. Several progeroid syndromes including mandibuloacral dysplasia type A (MADA), mandibuloacral dysplasia type B(MADB), Hutchinson-Gilford progeria (HGPS) and mandibular hypoplasia, deafness, and lipodystrophy syndrome (MDPL) have been reported previously. A novel MAD progeroid syndrome (MADaM) has recently been reported. So far, 7 cases of MADaM diagnosed with molecular diagnostics have been reported in worldwide. In the Chinese population, cases of MAD associated with the MTX2 variant have never been reported.The clinical symptoms and the genetic analysis were identified and investigated in patients presented with the disease. In addition, we analyzed and compared 7 MADaM cases reported worldwide and summarized the progeroid syndromes reported in the Chinese population to date.The present study reports a case of a novel homozygous mutation c.378 + 1G > A in the MTX2 gene, which has not been previously reported in the literature. Patients present with early onset and severe symptoms and soon after birth are found to have growth retardation. In addition to the progeroid features, skeletal deformities, generalized lipodystrophy reported previously, and other multisystem involvement, e.g. hepatosplenic, renal, and cardiovascular system, this case was also reported to have combined hypogammaglobulinemia. She has since been admitted to the hospital several times for infections. Among 22 previously reported progeroid syndromes, 16/22 were MADA or HGPS caused by LMNA gene mutations, and the homozygous c.1579C > T (p.R527C) mutation may be a hot spot mutation for MAD in the Chinese population. MAD and HGPS mostly present in infancy with skin abnormalities or alopecia, MDPL mostly presents in school age with growth retardation as the first manifestation, and is often combined with an endocrine metabolism disorder after several decades.gene reported in the Chinese population. MTX2 gene c.378 + 1G > A homozygous mutation has not been previously reported and the report of this patient expands the spectrum of MTX2 mutations. In addition, we summarized the genotypes and clinical characteristics of patients with progeroid syndromes in China.